Credit rationing in small firm-bank relationships - Kirschenmann, Karolin (Journal of Financial Intermediation, 2016)
I study credit rationing in small firm-bank relationships by using a unique data set of matched loan applications and contracts. I establish the degree of credit rationing by relating a firm's requested loan amount to the bank's granted amount. In line with theoretical predictions, credit rationing is higher for opaque than transparent firms at the beginning of their bank relationships and decreases over time for both. After testing for several alternative explanations, the results suggest that information and incentive problems explain the observed credit rationing and its dynamics.